Brain–Computer Interfaces for Treatment of Focal Dystonia. Issue 9 (10th August 2022) - Simonyan, Kristina; Ehrlich, Stefan K.; Andersen, Richard; Brumberg, Jonathan; Guenther, Frank; Hallett, Mark; Howard, Matthew A.; Millán, José del R.; Reilly, Richard B.; Schultz, Tanja; Valeriani, Davide
Abstract : Task‐specificity in isolated focal dystonias is a powerful feature that may successfully be targeted with therapeutic brain–computer interfaces. While performing a symptomatic task, the patient actively modulates momentary brain activity (disorder signature) to match activity during an asymptomatic task (target signature), which is expected to translate into symptom reduction.